1997
DOI: 10.1017/s0950268897007929
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Escherichia coli O157[ratio ]H7 in dairy cattle and the dairy farm environment

Abstract: The persistence of Escherichia coli O157:H7 in cattle and the farm environment was investigated on eight Ontario dairy farms positive for E. coli O157:H7 in a longitudinal study commenced one year previously. Faecal samples from cows, calves, humans, cats, rodents, wild birds, a composite fly sample and numerous composite and individual environmental samples were cultured and tested for verotoxin-producing E. coli (VTEC). VTEC isolates were serotyped and E. coli O157:H7 isolates were phage typed. E. coli O157:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
81
0
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 28 publications
13
81
0
2
Order By: Relevance
“…1). These findings agree with data reported by Blanco et al Efforts should be focused on infection control in order to reduce the prevalence of such microorganisms (40). According to Kudva et al (28), Escherichia coli O157 may survive at least six weeks in feces and possibly multiply in this material.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…1). These findings agree with data reported by Blanco et al Efforts should be focused on infection control in order to reduce the prevalence of such microorganisms (40). According to Kudva et al (28), Escherichia coli O157 may survive at least six weeks in feces and possibly multiply in this material.…”
Section: Resultssupporting
confidence: 89%
“…These include stress prevention, controlling food and water quality, as well as feedlot conditions and contact between adult and young animals (40).…”
Section: Resultsmentioning
confidence: 99%
“…However, it also seems true that individual animals may shed multiple strains simultaneously, and the spectrum of types changes over time (7). Some studies have indicated that E. coli O157 strains seem to be continually replaced by new and distinct types in cattle (4,13). This agrees with the results in our study, where on several occasions, animals appeared to shed different types at different times.…”
Section: Continued On Following Pagesupporting
confidence: 93%
“…Cooked ground beef, cow milk, dairy products, and so on are thought to be the major sources of EHEC infection [4,26,27], and cattle and other ruminants, such as sheep and goats, are known to harbor the organisms in their faeces and are regarded as natural reservoirs of the organisms [2,3,5,22,25]. The prevalence of EHEC O157 in cattle has been reported to be 0.2-60.4% in the United States [10,13,23,28], 1.9% in Australia [7], and 4.2-66.7% in Europe [5,6,16,24].…”
Section: Shiga Toxin (Stx)-producing Escherichia Coli (Stec) Ismentioning
confidence: 99%